Facile fabrication of paper-based analytical devices for rapid and highly selective colorimetric detection of cesium in environmental samples. Issue 76 (16th October 2017) - Kang, Sung-Min; Jang, Sung-Chan; Haldorai, Yuvaraj; Vilian, A. T. Ezhil; Rethinasabapathy, Muruganantham; Roh, Changhyun; Han, Young-Kyu; Huh, Yun Suk
Abstract : Cesium (Cs), a radioactive contaminant of the ecosystem, causes a major risk to human health and environments. This chemo-indicator is designed to exhibit a powerful detection capability featuring high selectivity and sensitivity to inactive Cs. Abstract : Cesium (Cs), a radioactive contaminant of the ecosystem, causes a major risk to human health and environments. Till now, the cesium sensor fabrication methods have been reported with the usage of expensive chemicals that are complex and time-consuming. In this work, we have fabricated a paper-based colorimetric device impregnated with a chrysoidine G (CG) as chemo-indicator which is simple, rapid, low-cost, and portable using a naked-eye quantitative technique for the detection and monitoring of inactive cesium in environmental analysis. This chemo-indicator is designed to exhibit a powerful detection capability featuring high selectivity and sensitivity to inactive Cs, by means of color discrimination from light yellow to red orange. Interestingly, a portable smart phone camera, which determined the relative red/green/blue (RGB) values within 3 s, provided us with further information on environmental pollution. Using our new colorimetric reusable sensor (CRS) platform, the CRS shows excellent detection linearity ( R 2 = 0.99) of inactive Cs from the contaminated water. Our results will pave the way for portable and versatile sensors and, in turn, for the detection and monitoring of toxic inactive cesium in contaminated water samples.